Pancreatic and salivary amylase/creatinine clearance ratios in normal subjects and in patients with chronic pancreatitis. Issue 5 (May 1978) - Hegarty, J E; O'Donnell, M D; McGeeney, K F; Fitzgerald, O
Abstract : The clearance of pancreatic and salivary amylase relative to creatinine was measured in 26 control subjects and 22 patients with chronic pancreatitis. Control values for pancreatic amylase clearance (+/- SD) were 2.64 +/- 0.86% compared with 1.54 +/- 0.95% for salivary amylase. In chronic pancreatitis, pancreatic amylase clearance ratios were significantly higher than controls (P less than 0.0005, mean 4.09 +/- 1.63 SD). The difference in clearance rate of salivary amylase did not reach a level of significance when compared with the control group. Twelve of the 22 patients showed pancreatic amylase clearance values above the normal limit of 4.4, while only five were abnormal when the clearance of total amylase was measured. The patients also showed statistically higher (P less than 0.0005) levels of serum salivary amylase when compared with 69 control sera. No such difference was found for the pancreatic component of serum amylase. Comparison of beta2-microglobulin clearance values showed no statistical difference between patients and controls.